THE PARTNERSHIP STRATEGY OF SCHOTERS BY RUANGGURU IN BUILDING BRAND AWARENESS THROUGH DIGITAL CANVASSING - Lyra (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2025)
This study aims to identify the partnership strategy of Schoters by Ruangguru in building brand awareness through digital canvassing activities and to analyze the implementation of the Integrated Marketing Communication (IMC) concept within this strategy. The background of this research arises from the increasing competition among global education service providers, which requires companies to strengthen brand awareness among partners and end audiences. This research employs a qualitative approach with a descriptive method. The subject of the study is the Strategic Partnership division of Schoters, while the research object includes partnership strategies and the implementation of digital canvassing activities. The main informant in this study is Malahati Shatadini, representing the Strategic Partnership division of Schoters. Data were collected through in-depth interviews, observation, and literature review. The data analysis technique uses the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results show that the partnership strategy and digital canvassing activities integrated with the IMC concept are proven effective in expanding partner networks, maintaining brand message consistency, and increasing Schoters’ brand awareness, although their effectiveness varies across different regions.